(untitled) (Journal of Humanitarian and Applied Sciences, 2026)
This study aimed to examine the relationship between exam anxiety and family support among secondary school students in Qasr Al-Akhyar, Libya, as well as to identify the levels of both variables within the study sample. The study adopted a descriptive-analytical approach. The population consisted of secondary school students in Qasr Al-Akhyar for the academic year 2025–2026, from which a random sample of 150 male and female students was selected. For data collection, the researcher used a two-dimensional questionnaire covering test anxiety and family support, with 10 items for each dimension measured using a dichotomous scale (Yes/No). Data were analyzed using percentages and Pearson’s correlation coefficient. The results indicated a moderate level of test anxiety among students, characterized by feelings of tension, fear, and difficulty concentrating. The findings also revealed a strong negative correlation between test anxiety and family support (r = -0.675), indicating that higher levels of family support are associated with lower levels of test anxiety.